The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/cid.12452
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evaluation of Implant Drill Made from Zirconium Dioxide

Abstract: PurposeZirconia is a good candidate material in the dental field. In this study, we evaluated biological responses against a zirconia drill using a bone cavity healing model.Materials and MethodsZirconia drills, stainless steel drills, and the drilled bone surface were observed by scanning electron microscopy (SEM), before and after cavity preparation. For the bone cavity healing model, the upper first and second molars of Wistar rats were extracted. After 4 weeks, cavities were prepared with zirconia drills o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Moreover, zirconia drills induce less damage during implant bed preparation and advantageous for bone healing [42]. Zirconia drills, when used for implant bed preparation positively influence bone healing compared to stainless steel drills [42]. We found the generation of friction heat during osteotomies for implant preparation to be influenced by the drill material especially when we prepare implant sites in dense cortical bone.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, zirconia drills induce less damage during implant bed preparation and advantageous for bone healing [42]. Zirconia drills, when used for implant bed preparation positively influence bone healing compared to stainless steel drills [42]. We found the generation of friction heat during osteotomies for implant preparation to be influenced by the drill material especially when we prepare implant sites in dense cortical bone.…”
Section: Discussionmentioning
confidence: 88%
“…The use of zirconia material is interesting because it has conductive abilities in the bone tissue, which are almost equivalent to those of titanium implants. Moreover, zirconia drills induce less damage during implant bed preparation and advantageous for bone healing [42]. Zirconia drills, when used for implant bed preparation positively influence bone healing compared to stainless steel drills [42].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the difference found in the meta-analysis of this review can be justified by the physical properties of Zr, such as low thermal conductivity, durability, and greater resistance ( Bayerlein et al, 2006 , Scarano et al, 2007 ). In the study by Akiba et al, 2017 after the drilling process, the Zr drills had sharper cutting edges, while the SS drills had greater damage. In addition, Zr drills produced a smoother and flatter bone surface, and were able to induce more effective bone healing than steel drills, suggesting that Zr is a material that presents more favorable conditions for establishing osseointegration.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, a blank lacunae area of 876.2 ± 48.4 µm was observed around the implant 14 days after heating with a minimal power output of HFED used in this study. However, because studies have demonstrated that empty osteocytic lacunae remain after stimulation by implant placement and drilling alone (Akiba et al., 2017; Haga et al., 2009), the surgical procedure may be considered to cause the blank lacunae area around the bone defect as a result of the stimulation by burs in addition to bone removal. Future studies should verify the effectiveness and safety of the thermoremoval method by comparing the results with those of groups who underwent removal by reverse torque or surgical procedure by burs.…”
Section: Discussionmentioning
confidence: 99%